Adalimumab for patients with Crohn's disease complicated by intra-abdominal abscess: a multicentre, prospective, observational cohort study. (22nd February 2019) - Pineton de Chambrun, G; Pariente, B; Seksik, P; Altwegg, R; Vuitton, L; Stefasnescu, C; Nancey, S; Aubourg, A; Serrero, M; Peyrin-Biroulet, L; Filippi, J; Viennot, S; et al.
Abstract: doi:10.1093/ecco-jcc/jjy222 Abstract P528 from the 'Poster presentations' section of the main abstract book has been withdrawn and re-inserted as DOP63 in the 'Late-breaking abstracts' section.